Autonomous production systems in virtual enterprises - Carvalho, Dinis (2005)
This paper presents the concept of Autonomous Production Systems (APS), which are the organizational units upon which enterprises can be built and managed in order to better face the globalization challenges. We believe that companies organized as networks of APS are better prepared to respond to the new economy challenges than organized in a hierarchical fashion. The way a traditional company can be reorganized in terms of a network of APS using decentralized management is also explored in this article. We propose an approach to create and operate Virtual Enterprises either based on APS or based on traditional companies. A Production Planning and Control system to operate Virtual Enterprises is also proposed in this paper using the concept of Bill Of Materials and Movements (BOMM).